Proceso de atención de enfermería en gestante de 28 semanas con diabetes gestacional. - Fernández Martínez, Julisa Mercedes (2021)
Gestational diabetes is a disease that develops only during pregnancy. Gestational diabetes can cause serious health problems in both the mother and the baby, being considered one of the main causes of maternal-fetal comorbidities. Symptoms can be mild, presenting with thirst and constant urge to urinate. The control and treatment of gestational diabetes is based primarily on diet and exercise according to needs and gestational status, in some cases subcutaneous insulin is used as a rescue measure to lower blood glucose levels. The risk factors that lead to the development of gestational diabetes are: the woman's age, African descent, a history of diabetes and hypertension in the family, being overweight during pregnancy, among others. First of all, the aforementioned presents the clinical case of a pregnant woman with 28 weeks of gestation diagnosed with gestational diabetes and who was admitted to the Basic Hospital of Playas, where the primary objective of nursing was to establish the Nursing Care Process (PAE), taking into account risk factors, clinical manifestations and altered functional patterns. It was possible to identify the nursing diagnosis through the NANDA, NOC, NIC taxonomy, thus applying the appropriate interventions to attend to all the aspects that compromised the health of the patient; risk factors included the mother's age, inadequate eating habits and sedentary lifestyle.